Large, low-field and reversible magnetostrictive effect in MnCoSi-based metamagnet at room temperature. (20th June 2021) - Liu, Jun; Gong, Yuanyuan; Zhang, Fengqi; You, Yurong; Xu, Guizhou; Miao, Xuefei; Xu, Feng
Highlights: The effect of element substitution on the tricritical behavior of MnCoSi is studied. Replacing Mn with Co is the most efficient way to reduce the critical field. Large reversible magnetostriction is achieved under low field at room temperature. The influence of valence electron concentration on the critical field is revealed. Abstract: TiNiSi-type MnCoSi-based alloys show large magnetostriction during the magnetic-field-induced metamagnetic transition. However, the high critical field required to drive the transition directly hinders their potential applications. In this work, we systematically investigate the tricritical behavior and magnetostrictive effect in substituted MnCoSi alloys. Replacing Si with Sb or In, Co with Fe or Cu, and Mn with Co, which can simultaneously reduce the critical field and the temperature of tricritical point, are explored. Among the substituted MnCoSi alloys, Mn0.983 Co1.017 Si displays a temperature of a tricritical point of 250 K and a room-temperature critical field of 0.60 T, which is the lowest up to now. Profited from these optimizations, a large reversible magnetostrictive effect under low field is successfully realized at room temperature. In a field of 1 T, the magnetostriction of Mn0.983 Co1.017 Si alloy is close to 1000 ppm. Besides, a strong relation between critical field and valence electron concentration is revealed in the transition-metal-substituted MnCoSi alloys. Our work greatly enhances the low-field magnetostrictive performance of MnCoSi-based alloys and make them be of interest in potential applications.